2000
DOI: 10.1136/gut.46.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Performance characteristics of magnetic resonance cholangiography in the staging of malignant hilar strictures

Abstract: Background-Magnetic resonance cholangiography (MRC) is currently under investigation for non-invasive biliary tract imaging.Aim-To compare MRC with endoscopic retrograde cholangiography (ERC) for pretreatment evaluation of malignant hilar obstruction. Methods-Twenty patients (11 men, nine women; median age 74 years) referred for endoscopic palliation of a hilar obstruction were included. The cause of the hilar obstruction was a cholangiocarcinoma in 15 patients and a hilar compression in five (one hepatocarcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
9

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(61 citation statements)
references
References 17 publications
2
49
0
9
Order By: Relevance
“…Indeed, several previous studies demonstrated that the accuracy of 2D-MRCP in assessing the level and feature of bile duct obstruction was comparable to that of ERCP/PTC (1,6,12,17,(22)(23)(24)(25)(26). However, at the same time, in several studies where surgical and pathological findings were used as a standard of reference, 2D-MRCP showed a relatively low accuracy regarding tumoral extent of the biliary tree (25)(26)(27). The determination of longitudinal tumor extension of bile duct cancer is one of the main challenges in MRC examinations due to the limited spatial resolution (in a range of 1.4 -2.5 mm resolution) of the MRC sequence, intrinsic complex anatomy of the bile duct near the perihilar region, and the superficial spreading of the bile duct tumors.…”
Section: D Mrcp In Malignant Obstructionmentioning
confidence: 96%
“…Indeed, several previous studies demonstrated that the accuracy of 2D-MRCP in assessing the level and feature of bile duct obstruction was comparable to that of ERCP/PTC (1,6,12,17,(22)(23)(24)(25)(26). However, at the same time, in several studies where surgical and pathological findings were used as a standard of reference, 2D-MRCP showed a relatively low accuracy regarding tumoral extent of the biliary tree (25)(26)(27). The determination of longitudinal tumor extension of bile duct cancer is one of the main challenges in MRC examinations due to the limited spatial resolution (in a range of 1.4 -2.5 mm resolution) of the MRC sequence, intrinsic complex anatomy of the bile duct near the perihilar region, and the superficial spreading of the bile duct tumors.…”
Section: D Mrcp In Malignant Obstructionmentioning
confidence: 96%
“…2) is an extremely useful screening investigation to estimate the extent of spread in the biliary tree [7]. MRI with contrast combined with MRC can provide the same information with respect to vascularity as compared to CT scan.…”
Section: Preoperative Assessmentmentioning
confidence: 99%
“…MRI with contrast combined with MRC can provide the same information with respect to vascularity as compared to CT scan. Information on involvement is useful in planning preoperative biliary drainage and type of surgery, and in case of inoperable tumours, approach to palliative stenting [7].…”
Section: Preoperative Assessmentmentioning
confidence: 99%
“…Há fortes indícios de que, nestes casos, a preferência seja drenar o segmento que foi contrastado durante o exame colangiográfico. Assim, através de CPRM, ZIDI et al (16) Vale ressaltar que a acurácia da ressonância para o estudo das via biliares não se repete para os ductos pancreáticos. Assim, novos métodos, tais como a pancreatorressonância dinâmica, feita com injeção de secretina, melhora a visibilização dos ductos pancreáticos (6) .…”
unclassified